2021
DOI: 10.1186/s12885-020-07740-1
|View full text |Cite
|
Sign up to set email alerts
|

TOP2A/MCM2, p16INK4a, and cyclin E1 expression in liquid-based cytology: a biomarkers panel for progression risk of cervical premalignant lesions

Abstract: Background To improve the efficiency of early diagnosis systems for cervical cancer, the use of cellular and viral markers for identifying precancerous lesions with a greater probability to progress to cancer has been proposed. Several cellular proteins and markers of oxidative DNA damage have been suggested as possible biomarkers of cervical carcinogenesis; however, they have not been evaluated together. In this study, we analyzed the expression of the cellular markers p16INK4a, Ki-67, CyclinE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 41 publications
4
10
0
Order By: Relevance
“…TOP2A overexpression was observed in 60.2% of squamous cell carcinoma and 83.3% of adenocarcinoma. Our findings agree with those reported by Del Moral-Hernández et al [ 24 ], which showed that increased expression of TOP2A/MCM2 biomarkers to approximately 3-times increased progression risk of HSIL to cervical cancer lesions. Similarly, TOP2A expression levels discriminated dysplastic and non-dysplastic FFPE cervical tissues with improved detection of CIN2+ [ 15 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…TOP2A overexpression was observed in 60.2% of squamous cell carcinoma and 83.3% of adenocarcinoma. Our findings agree with those reported by Del Moral-Hernández et al [ 24 ], which showed that increased expression of TOP2A/MCM2 biomarkers to approximately 3-times increased progression risk of HSIL to cervical cancer lesions. Similarly, TOP2A expression levels discriminated dysplastic and non-dysplastic FFPE cervical tissues with improved detection of CIN2+ [ 15 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…In a multivariate logistic regression model, the age-adjusted OR for predicting cervical cancer lesions were independently significant for p16/TOP2A biomarkers in archived FFPE cervical tissues [p16: OR = 1.142 (95% CI: 1.059–1.232, p <0.001) and TOP2A: OR = 1.046 (95% CI: 1.008–1.085, p = 0.015)]. These findings corroborate with previously reported studies that used cervical scraps/ FFPE tissues, which showed that progression of LSIL/CIN-1 to cervical cancer lesions was conferred by p16, TOP2A, p16 and TOP2A [ProEx C] [ 24 , 38 , 39 ]. However, our results herein disagree with those reported by Peres et al [ 22 ], that high TOP2A expression levels were observed in cervical smear samples than in cervical biopsies.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations